2011
DOI: 10.4161/auto.7.7.15279
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the involvement of LC3B and GATE-16 in p62 recruitment into autophagosomes

Abstract: Autophagy is a major intracellular trafficking pathway that delivers proteins and organelles from the cytoplasm into lysosomes for consequential degradation and recycling. Mammalian Atg8s are key autophagic factors that undergo a unique ubiquitin-like conjugation to the lipid phase of the autophagosomal membrane. In addition to their activity in autophagosome formation, several Atg8s directly bind p62/SQSTM1. Here we show that LC3 and GATE-16 differ in their mode of p62 binding. While the soluble form of both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 15 publications
2
41
0
Order By: Relevance
“…Our findings indicated that FAS interacts with Atg8 in an N-terminaldependent manner. The N terminal of Atg8 reportedly participates in adaptor recruitment and protein recognition (15,16). FAS degradation was indeed found to be dependent on its interaction with Atg8, further supporting selective degradation.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Our findings indicated that FAS interacts with Atg8 in an N-terminaldependent manner. The N terminal of Atg8 reportedly participates in adaptor recruitment and protein recognition (15,16). FAS degradation was indeed found to be dependent on its interaction with Atg8, further supporting selective degradation.…”
Section: Discussionmentioning
confidence: 72%
“…Atg8 is a key factor in the selective delivery of cargo proteins for degradation. The N-terminal region of Atg8 has been shown to participate in adaptor recruitment and protein recognition (15,16). In searching for potential cargo or machinery proteins that interact with Atg8, we performed immunoprecipitation experiments on Atg8-null cells transformed with GFP-Atg8 or with GFP-Atg8 lacking the first (GFP-Atg8ΔN8) or both (GFP-Atg8ΔN24) N-terminal α-helices.…”
Section: Fas Is Preferentially Degraded By Autophagy Under Nitrogen Smentioning
confidence: 99%
“…The autophagy receptor p62/SQSTM1 binds very well to all ATG8 family proteins in in vitro binding studies. However, for selective autophagy of p62/SQSTM1, it has been found that LC3B is required and not the GABARAP subfamily (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…p62 binds to both soluble LC3 and GATE-16, but it interacts only with lipidated LC3, not lipidated GATE-16 (23). Thus, the recruitment of p62 into autophagosomes specifically depends on LC3.…”
mentioning
confidence: 99%